Priorities for Public Health and Wellness in the Face of Economic Challenges Caused by the Prevalence of Chronic Diseases - Akhtar, Md. Tanwir (Journal of Posthumanism, 2025)
The prevalence of chronic diseases is rising worldwide, which poses a severe threat to emerging countries' efforts to enhance public health. There are easily accessible, affordable, and very effective ways to avoid chronic illnesses; the inability to act is now more of a political than a technical problem. Chronic illness is now the most common cause in many developing countries despite being frequently linked to industrialized nations. Threats to population health are of particular concern to many low- and middle-income countries. In addition to undernutrition, bad diets and lifestyle choices are the root cause of nonfatal illnesses. This project discusses the direct and considerable impact that the fast growth of chronic diseases, the shortage of pharmaceutical products, the supply chain, and medical services have on overcoming the problems facing economic development. This makes research and development emphasizing health and wellness a primary goal.